PCRRFLP of the ribosomal DNA internal transcribed spacers (ITS) provides markers for the A and B genomes in Musa L. - Nwakanma, D.C.; Pillay, M.; Okoli, B.E.; Tenkouano, A. (Springer, 2003)
Musa acuminata Colla (AA genomes) and Musa balbisiana Colla (BB genomes) are the diploid ancestors of modern bananas that are mostly diploid or triploid cultivars with various combinations of the A and B genomes, including AA, AAA, BB, AAB and ABB. The objective of this study was to identify molecular markers that will facilitate discrimination of the A and B genomes, based on restriction-site variations in the internal transcribed spacers (ITS) of the nuclear ribosomal RNA genes. The ITS regions of seven M. acuminata and five M. balbisiana accessions were each amplified by PCR using specific primers. All accessions produced a 700-bp fragment that is equivalent in size to the ITS of most plants. This fragment was then digested with ten restriction enzymes (AluI, CfoI, DdeI, HaeIII, HinfI, HpaII, MspI, RsaI, Sau3AI and TaqI) and fractionated in 2% agarose gels, stained with ethidium bromide and visualized under UV light. The RsaI digest revealed a single 530-bp fragment unique to the A genome and two fragments of 350-bp and 180-bp that were specific to the B genome. A further 56 accessions representing AA, AAA, AAB, AB and ABB cultivars, and synthetic hybrids, were amplified and screened with RsaI. All accessions with an exclusively A genome showed only the 530-bp fragment, while accessions having only the B-genome lacked the 530-bp fragment but had the 350-bp and 180-bp fragments. Interspecific cultivars possessed all three fragments. The staining intensity of the B-genome markers increased with the number of B-genome complements. These markers can be used to determine the genome constitution of Musa accessions and hybrids at the nursery stage, and, therefore, greatly facilitate genome classification in Musa breeding.